2019
DOI: 10.1158/1541-7786.mcr-19-0429
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Role for Calcium Signaling in Colorectal Cancer Development and Progression

Abstract: Clinical data suggest that many malignant cancers are associated with hypercalcemia. Hypercalcemia can facilitate the proliferation and metastasis of gastric and colon tumors, and has been considered a hallmark of end-stage disease. However, it has also been reported that dietary calcium or vitamin D supplementation could reduce the risk of many types of cancers. In particular, the intestines can absorb considerable amounts of calcium via Ca 2þ -permeable ion channels, and hypercalcemia is common in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 86 publications
0
21
0
1
Order By: Relevance
“…On the other side of the association with inflammation, calcium may promote cancer in other ways. First, calcium has been shown to be involved in cell differentiation and proliferation through modulating cell signaling that can commonly initiate colorectal carcinogenesis, such as APC/ β-catenin and Hedgehog pathways (34)(35)(36)(37), and it has been proposed that hypercalcemic environment may help colon adenocarcinoma cells develop (38). Second, patients with bone metastasis are well known to be hypercalcemic (39) suggesting that patients with elevated serum calcium and worse survival might have undiagnosed metastatic disease before the curative-intent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side of the association with inflammation, calcium may promote cancer in other ways. First, calcium has been shown to be involved in cell differentiation and proliferation through modulating cell signaling that can commonly initiate colorectal carcinogenesis, such as APC/ β-catenin and Hedgehog pathways (34)(35)(36)(37), and it has been proposed that hypercalcemic environment may help colon adenocarcinoma cells develop (38). Second, patients with bone metastasis are well known to be hypercalcemic (39) suggesting that patients with elevated serum calcium and worse survival might have undiagnosed metastatic disease before the curative-intent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium overload can activate many channels and factors related to calcium ions. Studies have shown that they can promote the proliferation, invasion, metastasis, and anti-apoptosis of tumor cells in CC [ 36 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the invasion and metastasis of CC are closely related to the level of intracellular Ca 2+ [ 36 ] and NCXs are important proteins involved in the regulation of cytoplasmic Ca 2+ , it is important to observe the expression of NCXs in CC and analyze the relationship between NCXs and CC. For this purpose, we collected 111 clinical cases of stage II–IV colonic tumor tissues and their distal colonic normal tissues and then measured the expression of NCX1, NCX2, and NCX3 by quantitative polymerase chain reaction (qPCR), western blotting (WB), and immunohistochemistry (IHC).…”
Section: Introducementioning
confidence: 99%
“…Although the biochemical and the clinical behavior of calcium with regard to CRC seem contrasting, calcium signaling promotes or inhibits cancer based on the ability of the tissue environment to maintain balance of its intra- and extracellular concentrations: the increase of intracellular calcium promotes cancer progression, but once the level has reached overload, cancer cell death is favored, deteriorating cancerous tissue. Although the clinical application of such behavior is not yet available, calcium channels may present as possible drug targets to reduce tumor burden [ 175 ].…”
Section: Micronutrients and Molecular Tuning Of Colorectal Carcinogenesismentioning
confidence: 99%